1990
DOI: 10.1104/pp.92.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol Acetyl Transferase (CAT) Protein Is Expressed in Transgenic Tobacco in Field Tests following Attack by Insects

Abstract: The expression of chloramphenical acetyl transferase (CAT) protein driven by the wound-inducible promoter from the proteinase inhibitor 11 K (pin2) gene was examined in whole tobacco (Nicotiana tabacum L.) plants under field conditions. Mechanical wounding of the field-grown leaves caused an accumulation of CAT protein in these leaves which begins several hours after wounding and continues to accumulate for about 36 hours. When sections of leaves were assayed for accumulation of CAT protein following wounding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Eventually, the levels of IAA decline by two-to threefold in the 24 h following the wound. The kinetics of this decline in IAA levels is very similar to the kinetics of activation of the proteinase inhibitor gene system in either normal tomato plants (13), or in transgenic tobacco plants (28). This decline in IAA levels in wounded tobacco foliage is consistent with a role of IAA in the regulation of the inhibitor II gene system.…”
Section: Plantssupporting
confidence: 64%
See 2 more Smart Citations
“…Eventually, the levels of IAA decline by two-to threefold in the 24 h following the wound. The kinetics of this decline in IAA levels is very similar to the kinetics of activation of the proteinase inhibitor gene system in either normal tomato plants (13), or in transgenic tobacco plants (28). This decline in IAA levels in wounded tobacco foliage is consistent with a role of IAA in the regulation of the inhibitor II gene system.…”
Section: Plantssupporting
confidence: 64%
“…When tobacco plants bearing thepin2-CAT gene were examined for their expression of CAT protein, they expressed CAT protein in a manner which was identical with the wild-type expression of proteinase inhibitor II in young tomato plants (26,28). Therefore, these plants make a good model system for the study of the wound-inducible genes.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chimeric PI-II-ipt gene codes for the first enzyme in the cytokinin biosynthetic pathway and its expression is regulated by the promoter from the PI-IIK gene [19,30,36]. Fusions with the /%glucuronidase or chloramphenicol acetyl transferase (CAT) reporter genes indicated that the PI-IIK promoter directs gene expression in tissues preferentially consumed by insects and that CAT gene expression in leaves of transgenic tobacco plants had no effect on the extent of leaf consumption by various insects [20,35,36]. Ten kanamycin-resistant, independently transformated shoots were chosen and grown to maturity.…”
Section: Analysis Of Transgenic Tobacco Plants For Woundinduced Exprementioning
confidence: 99%
“…99,1992 inducible gene, we chose as our starting material a line of transgenic tobacco, Tr25, that contains a pin2-CAT construct (31). These plants show high levels of wound-inducible CAT activity from the transgene and have been well characterized (32).…”
Section: Isolation Of Ump Synthase Mutantsmentioning
confidence: 99%